Clinical Experience With the Subcutaneous Implantable Cardioverter–Defibrillator in Adults With Congenital Heart Disease. (September 2016) - Moore, Jeremy P.; Mondésert, Blandine; Lloyd, Michael S.; Cook, Stephen C.; Zaidi, Ali N.; Pass, Robert H.; John, Anitha S.; Fish, Frank A.; Shannon, Kevin M.; Aboulhosn, Jamil A.; Khairy, Paul
Abstract : Background—: Sudden cardiac death is a major contributor to mortality for adults with congenital heart disease. The subcutaneous implantable cardioverter–defibrillator (ICD) has emerged as a novel tool for prevention of sudden cardiac death, but clinical performance data for adults with congenital heart disease are limited. Methods and Results—: A retrospective study involving 7 centers over a 5-year period beginning in 2011 was performed. Twenty-one patients (median 33.9 years) were identified. The most common diagnosis was single ventricle physiology (52%), 9 palliated by Fontan operation and 2 by aortopulmonary shunts: d -transposition of the great arteries after Mustard/Senning (n=2), tetralogy of Fallot (n=2), aortic valve disease (n=2), and other biventricular surgery (n=4). A prior cardiac device had been implanted in 7 (33%). The ICD indication was primary prevention in 67% and secondary in 33% patients. The most common reason for subcutaneous ICD placement was limited transvenous access for ventricular lead placement (n=10) followed by intracardiac right-to-left shunt (n=5). Ventricular arrhythmia was induced in 17 (81%) and was converted with ⩽80 Joules in all. There was one implant complication related to infection, not requiring device removal. Over a median follow-up of 14 months, 4 patients (21%) received inappropriate and 1 (5%) patient received appropriate shocks. There was one arrhythmic death related to asystole in a single ventricle patient. Conclusions—: Subcutaneous ICD implantation is feasible for adults with congenital heart disease patients. Most candidates have single ventricle heart disease and limited transvenous options for ICD placement. Despite variable anatomy, this study demonstrates successful conversion of induced ventricular arrhythmia and reasonable rhythm discrimination during follow-up.